Remedying the uncertainty surrounding penalties and liquidated damages: Denka Advantech Pte Ltd v Seraya Energy Pte Ltd [2021] 1 SLR 631 - TAN, Qing Zhe (Institutional Knowledge at Singapore Management University, 2022)
In Singapore, the authority for penalty clauses had always been the seminal case of Dunlop Pneumatic Tyre Company, Limited v New Garage and Motor Company, Limited (“Dunlop”).